Peran Penyuluh Agama Islam dalam Bimbingan Pernikahan Calon Pengantin di KUA Jekan Raya - Nadhrah 'Afifah Dzalqi; Arini Safitri; Nor Fatmah (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study is based on the role of Islamic religious instructors in marriage guidance for prospective brides and grooms at the Jekan Raya Religious Affairs Office. The role of religious instructors has a strategic position to equip couples in building a household that is sakinah, mawaddah, and rahmah. In its implementation, instructors have an important role as inspirators, motivators, catalysts, stabilizers, facilitators, and government employees. This study aims to determine the role of Islamic religious instructors in marriage guidance for prospective brides and grooms at the Jekan Raya Religious Affairs Office, as well as to identify supporting and inhibiting factors in carrying out this role. The method used in this study is a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that religious instructors have carried out their roles in accordance with their duties and functions, namely providing guidance that includes religious, psychological, and social aspects. However, there are several inhibiting factors such as time constraints and lack of understanding of participants, as well as supporting factors such as the instructor's scientific background and communication skills, and empathy. The conclusion of this study is that the role of Islamic religious instructors is very important in the success of the marriage guidance program, but the effectiveness of its implementation is greatly influenced by supporting and inhibiting factors in the field.